Lessons in place: Thoreau and Indigenous philosophy. (Metaphilosophy, 2022)
Some have argued that Indigenous and European Americans learned much from each other along the border. This paper examines the fate of the influence of Indigenous philosophy by considering the work of Henry David Thoreau. First, it summarizes the argument of Native Pragmatism: Rethinking the Roots of American Philosophy about the influence of Indigenous thought on American philosophy. In the second section, it discusses American philosophies of resistance in relation to the process of colonization. In the third, it considers the later work of Thoreau as an example of the declining influence of Native thought on nineteenth‐century American philosophy. On one hand, Thoreau adopted a philosophy of place that seems to emerge directly from his experiences with Indigenous Americans. On the other, he overtly sets aside the Indigenous conception of relational agency in favor of a Romantic conception of individuals over against both nature and civilization.